'So what made you decide to become a school librarian?' Reasons people currently working in New Zealand school libraries give for their choice of employment. (June 2016) - Walker, Lynn; Calvert, Philip
It is an exciting time to be a school librarian, but there are concerns about possible shortages in the profession in the not too far distant future, as the 'baby-boomer' generation currently working in schools approaches retirement. In order to attract and retain suitably qualified new recruits to the profession, this study examines the reasons why people choose this area of librarianship. Using Herzberg's motivation theory in the world of work as a framework, nine librarians currently employed in secondary schools were interviewed about their reasons for choosing school librarianship as a profession. This qualitative study concludes that for most women school librarianship is a conscious lifestyle choice, as the availability of flexible hours offers superior work/life balance. Other factors are the environment, plus the people, and the job itself which offers autonomy, variety, and immensely satisfying work. The two major sources of dissatisfaction are pay and conditions of employment.